PENERAPAN SISTEM INFORMASI MANAJEMEN BERBASIS TEKNOLOGI DI BADAN KEPEGAWAIAN SERTA PENDIDIKAN DAN PELATIHAN KABUPATEN MINAHASA UTARA - PONTOH, RIZKY PRATAMA; POSUMAH, JOHNNY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2022)
The need for quality public services is a must for public organizations today so that it is theresponsibility of the government to be able to make adjustments in order to improve quality public services.The use of information systems in real services can be seen as to carry out service functions, this is what ismeant by an information system. The purpose of this research is to find out how the Application ofTechnology-Based Management Information System in the Agency for Personnel and Education andTraining of North Minahasa Regency. The research method used is descriptive research with a qualitativeapproach. Informants in research are people who can provide information about research. The focus ofthe research is seen from the indicators according to Kumorotomo which suggests that a computer-basedmanagement information system contains elements, namely humans, hardware and software, data andprocedures. Data collection techniques through observation, interviews and documentation. The results ofthe study show that the Personnel and Education and Training Agency has the responsibility to use andimplement a technology-based information system which is given the responsibility for managing thepersonnel system as well as education and training activities for all employees but has not been able to runand implement a technology-based information system. Limited facilities, technology systems, employeecapabilities and budgetary support are the current challenges.Keywords : Implementation, Management Information System, Personnel Agency and Education andTraining